Multi-objective Sustainability Assessment of Levulinic Acid Production from Empty Fruit Bunch - Hafyan, R.H. (Springer, 2020)
Malaysia is one of the largest producers of crude palm oil, which also produces abundant empty fruit bunch (EFB) as a lignocellulosic waste. Levulinic acid (LA) is a promising chemical building block that can be produced from acid-hydrolysed EFB, via dehydration-hydration reactions. This work has evaluated the sustainability aspects of LA production by simultaneously considering economic, environment, and safety aspects. These aspects were computed using net present value (NPV), global warming potential (GWP), and hazard identification and ranking (HIRA), respectively. Using HIRA, fire and explosion damage index (FEDI) and toxicity damage index (TDI) were also estimated. These conflicting objectives were solved using multi-objective optimization. Genetic algorithm (GA) was conducted in MATLAB to generate a Pareto-optimal front. The results show trade-offs among the objective functions and insights into how design/operating variables affect the sustainability aspects. The Pareto-optimal solutions reveal that at maximum EFB capacity of 100 ton/h, maximum NPV of 6.4 billion USD is achieved. However, at this point, the values of GWP and TDI are at a maximum of 174,041Â kgÂ CO2-eq and 402.9, respectively. At minimum EFB capacity of 50 ton/h, only minimum NPV of 2.7 billion USD is achieved. Nevertheless, at this point, the values of GWP and TDI are at a minimum of 86,691Â kgÂ CO2-eq and 283.3, respectively. Â© 2019, Springer Nature Singapore Pte Ltd.